Common Mistakes in Wrist and Hand Trauma - Smithuis, Frank F.; Groepenhoff, Floor; Vuurberg, Gwendolyn; Maas, Mario (Seminars in Musculoskeletal Radiology, 2025)
The anatomy of the wrist and hand is complex due to small and closely opposed bone and soft tissue structures. The complexity of the wrist and hand anatomy simultaneously allows a wide range of motion yet also makes these joints vulnerable to injury. The large number of potentially involved structures can make adequate evaluation of the traumatized wrist challenging. Injury to the wrist or hand is often significant because of the risk of permanent functional impairment.Additionally, traumatic injury can be easily overlooked because signs may be subtle on conventional radiology and satisfaction of search poses risk of incomplete assessment. Other potential factors that create risk of errors in wrist assessment are nonstandardized acquisition, overlooking subtle signs of osseous trauma, neglecting soft tissue trauma, not performing additional imaging despite persistent suspicion of traumatic injury, traumatic injury, and misinterpretation of normal variants and trauma mimics.Thus adequate clinical information on the radiology request is essential to initiate an optimized imaging strategy to detect fractures or dislocations and identify normal variants. This review offers examples of pitfalls when assessing conventional radiographs of the wrist and recommendations on when additional imaging using ultrasound, computed tomography, or magnetic resonance imaging is needed.
Keywords: wrist trauma; hand trauma; fall on an outstretched hand; radiography; trauma mimics